Motivating and Retaining Employees in the Chinese Retail Industry: In-depth Case Study - Su, Hang (2008)
Motivating and retaining the key employees have been the major issues facing by many organizations in China today. The study attempts to investigate the Chinese retail sector for its related human resource management problems on employee motivation and retention.